2015
DOI: 10.1007/s12034-015-0915-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the microstructure and mechanical properties of multi-pass PCGTA welding of super-duplex stainless steel

Abstract: This paper addresses the weldability, microstructure and mechanical properties of the multi-pass welding of super-duplex stainless steel (SDSS). Pulsed current gas tungsten arc welding (PCGTAW) was carried out employing ER2553 and ERNiCrMo-4 fillers. Microstructure examination showed the presence of austenite in different forms at the weld zone of ER2553 whereas multi-directional grain growth was observed for ERNiCrMo-4 welds. Tensile and impact studies corroborated that the weldments employing ER2553 exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The TEM graph and corresponding diffraction pattern of the nitrides revealed the rod-like chromium nitride Cr 2 N, as shown in Figure 9 . Either chromium nitride or γ 2 suppresses the corrosion resistance of DSSs, but γ 2 can improve the toughness of weld joints while chromium nitrides are harmful to the toughness [ 27 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TEM graph and corresponding diffraction pattern of the nitrides revealed the rod-like chromium nitride Cr 2 N, as shown in Figure 9 . Either chromium nitride or γ 2 suppresses the corrosion resistance of DSSs, but γ 2 can improve the toughness of weld joints while chromium nitrides are harmful to the toughness [ 27 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed an increasing in the weld depth without affecting the mechanical properties of the specimens [30,31]. Other studies were dedicated to microstructure and mechanical properties [32][33]. In this work, 13 oxides were investigated on 316L austenitic stainless steel.…”
Section: Introductionmentioning
confidence: 98%
“…The calculated sigma phase volume percentages from cooling rates of 4 °C/s, 2.5 °C/s, and 1 °C/s exhibited excellent agreement with the physical simulator experimental results using these cooling rates. The microstructure behaviors and mechanical characteristics of SDSS after the multi-pass PCGTA joining process were analyzed by Ramkumar et al 15 It was reported that with the matching filler wire in comparison to the over-alloyed filler the high and enhanced properties for weld samples will be obtained. Santos et al 16 studied the microstructure variation and mechanical characteristics of DSS and SDSS during the friction stir welding process.…”
Section: Introductionmentioning
confidence: 99%